An integrated approach to identifying and characterising resilient urban food systems to promote population health in a changing climate. Issue 13 (10th April 2015) - James, Sarah W; Friel, Sharon
Abstract: Objective: To determine key points of intervention in urban food systems to improve the climate resilience, equity and healthfulness of the whole system. Design: The paper brings together evidence from a 3-year, Australia-based mixed-methods research project focused on climate change adaptation, cities, food systems and health. In an integrated analysis of the three research domains – encompassing the production, distribution and consumption sectors of the food chain – the paper examines the efficacy of various food subsystems (industrial, alternative commercial and civic) in achieving climate resilience and good nutrition. Setting: Greater Western Sydney, Australia. Subjects: Primary producers, retailers and consumers in Western Sydney. Results: This overarching analysis of the tripartite study found that: (i) industrial food production systems can be more environmentally sustainable than alternative systems, indicating the importance of multiple food subsystems for food security; (ii) a variety of food distributors stocking healthy and sustainable items is required to ensure that these items are accessible, affordable and available to all; and (iii) it is not enough that healthy and sustainable foods are produced or sold, consumers must also want to consume them. In summary, a resilient urban food system requires that healthy and sustainable food items are produced, that consumers can attain them and that they actually wish to purchase them. Conclusions: This capstone paper found that the interconnected nature of the different sectors in the food system means that to improve environmental sustainability, equity and population health outcomes, action should focus on the system as a whole and not just on any one sector.